Analisis Pemilihan Moda Transportasi Penduduk Kelurahan Pabuaran-Cibinong Pasca Pengoperasian Kereta Komuter (KRL) Jalur Nambo (Cibinong) – Citayam – Jakarta - Rosnaeni, Rosnaeni; Buchori, Imam (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
Congestion in Cibinong areas is mainly caused by highly vehicle usage, while the supply of road network is very limited. therefore it is needed a modal shift from private vehicles and optimizing the role of mass public transport (railway). This study aims to determine the modal choice of Pabuaran community, after the operational of commuterline (KRL) lane Nambo (Cibinong) - Citayam - Jakarta. This study uses a simple descriptive method to identify the factors that influence the mode choice of Pabuaran community, crosstab analysis method to identifying the movement of population, and binary logistic models to analyze the probability the change transport modes of Pabuaran community. The result of this study show that the probability of potential users for using commuterline are 91%, it is influenced by several factors such as the distance of the settlement to the station, travel time, travel expenses, employment status and the existence of public transport/feeder to the station. The improvement of railway services in Cibinong station such as an increase in the frequency, timeliness, travel time, expected to attract the community to using rail services in their activities.